2021
DOI: 10.1177/0379572121998127
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Contribution of the Health System to Reducing Stunting in SUN Countries

Abstract: Background: The global nutrition community has called for a multisectoral approach to improve nutritional outcomes. While most essential nutrition interventions are delivered through the health system, nutrition-sensitive interventions from other sectors are critical. Objective: We modeled the potential impact that Scaling Up Nutrition (SUN) interventions delivered by the health system would have on reaching World Health Assembly (WHA) stunting targets. We also included results for targets 2, 3, and 5. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…According to this study, a cross-sector approach has been termed 'Health in All Policies' implying multisectoral collaboration, which integrates various efforts from different stakeholders both within and outside health sectors [57,58]. Other studies have also shown the importance of collaboration between the health sector and other sectors [59,60]. The 2020-2023 USAID report on advancing nutrition in Tanzania has shown a close collaboration between the government and international organizations in supporting efforts towards the elimination of malnutrition in the country.…”
Section: Discussionmentioning
confidence: 99%
“…According to this study, a cross-sector approach has been termed 'Health in All Policies' implying multisectoral collaboration, which integrates various efforts from different stakeholders both within and outside health sectors [57,58]. Other studies have also shown the importance of collaboration between the health sector and other sectors [59,60]. The 2020-2023 USAID report on advancing nutrition in Tanzania has shown a close collaboration between the government and international organizations in supporting efforts towards the elimination of malnutrition in the country.…”
Section: Discussionmentioning
confidence: 99%